(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Some people used herbal extracts as a treatment for diabetes mellitus worldwide. Such treatment of considerable benefit especially during the early stages of the illness. Many phytoconstituents responsible for anti diabetic effects have been isolated from hypoglycemic plants; one of which is Foeniculum vulgare. Objective:To investigate the effects of alcoholic extract of Foeniculum vulgare on some biochemical parameters in liver and kidneys of alloxan-induced diabetic mice, in order to use this herb as natural products to the management of diabetes mellitus. Methods: Twenty four female mice (18 diabetic mice and 6 control) were divided into 4 groups, each contain 6 mice (I = control, II = alloxan-treated miceI, III and IV = extract treated mice). Oral administration of Foeniculum vulgare extract given for 30 days to group III and IV in doses of 1.2 mg/kg BW) and 2.2 mg/kg BW, respectively. The serum glucose, insulin, lipid profile, glutamate oxaloacetate transaminase, glutamate pyruvate transaminase, alkalinposphatase, creatinine, urea and calcium, were measured in fasting state. Results:As compared with group II, serum glucose was significantly reduced and serum insulin significantly elevated in groups III and IV following oral administration of extract for 21 days. Following 30 days, significant reduction in the total cholesterol, triglycerides, low density lipoprotein- cholesterol, glutamate oxaloacetate transaminase, glutamate pyruvate transaminase, alkaline phosphatase, very low density lipoprotein- cholesterol, and creatnin, whereas high density-cholesterol and calcium were significantly increased. Conclusion: Foeniculum vulgare extract have good hypoglycemic, antihyperlipidemic in Alloxan- induced diabetic mice, in addition to the improvement in the glutamate oxaloacetate transaminase, glutamate pyruvate transaminase, alkaline phosphatase, creatinin, urea and calcium. Keywords:Diabetes militates, Antihyperlipidemia, Hypoglycemic effect, alloxan, medical plants, Foeniculum Vulgare.